Towards Achieving the Aims of NEP 2020: Enablers for Effective Learning in an Online Teacher Professional Development Programme on Experiential Learning Pedagogy - Patwardhan, Mrinal; Abrol, Bobby (Voices of Teachers and Teacher Educators, 2023)
This research artice presents the findings from a year-long evaluation research study conducted for the online certificate course on "Experiential Learning for 21st Century' for Eklavya Model Residential School teachers across den states of India designed to advance the aims of NEP 2020. The course design was built upon four cornerstones - course content presenting pedagogy-in-action, active and collaborative learning opportunities for teachers during the course, technology integration for seamless course delivery and feedback-based reflective scaffolding. The study used a mixed research method, and data was collected through interviews with stakeholders, survey forms, focus group discussions, class observations, school visits, reflection reports and lesson plan-qualitative evaluation. The findings revealed that the design of a Teacher Professional Development (TPD) Programme should address the questions about what is the nature of teachers' knowledge and how teachers learn. During the online certificate course, teachers embraced the principles of experiential learning pedagogy and created engaging learning experiences for their students. The research study identified the features that positively influenced teachers' learning of a new pedagogy during the course. The paper presents the study findings as recommendations for educators/educationists and government officials interested in facilitating and enhancing teachers' learning from a TPD Programme.